Where are We going? Overview of Major Collaborative Conservation Research Projects and Implications for the Future Preservation of Collections - Palm, Jonas (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2005)
In this paper I will tell you about some research and strategic projects, some of them at the end of their time and some just started. Although digitisation seems to have been a major topic in archives and libraries since the mid 1990s the vast majority of the collections are still based on traditional, i.e. analogue, media. The preservation problems much discussed prior to this still exist and still present some major hazards. What differs today from yesterday is that the technological progress has given us new means within reasonable costs to perform research and develop new tools as well as improve the monitoring of decay.